2017
DOI: 10.21101/cejph.a4438
|View full text |Cite
|
Sign up to set email alerts
|

A 12-year Trend of Psychological Distress: National Study of Finnish University Students

Abstract: SUMMARYObjective: The study aimed to explore changes in the prevalence of psychological distress and co-occurring psychological symptoms among 19-34 years old Finnish university students between the years 2000 and 2012.Methods: The prevalence of perceived frequent psychological symptoms was compared in four nationwide cross-sectional student health surveys with random samples (N = 11,502) Results: In the time phase from 2000 to 2012, the overall psychological distress (12-item General Health Questionnaire, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
(40 reference statements)
2
27
0
Order By: Relevance
“…However, past studies have suggested that poor sleep hygiene practices among students may contribute to the reduced sleep quality (Gellis et al, 2014). Worsening of sleep habits (greater discrepancies between timing for sleep in weekdays compared with weekends) in the general population over time (Sivertsen, Overland, & Pallesen, 2011), the sharp increase in the availability and use of electronic devices (Suganuma et al, 2007), as well as the increase in psychological problems among university students (Oksanen, Laimi, Bjorklund, Loyttyniemi, & Kunttu, 2017) are some possible explanations to these findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, past studies have suggested that poor sleep hygiene practices among students may contribute to the reduced sleep quality (Gellis et al, 2014). Worsening of sleep habits (greater discrepancies between timing for sleep in weekdays compared with weekends) in the general population over time (Sivertsen, Overland, & Pallesen, 2011), the sharp increase in the availability and use of electronic devices (Suganuma et al, 2007), as well as the increase in psychological problems among university students (Oksanen, Laimi, Bjorklund, Loyttyniemi, & Kunttu, 2017) are some possible explanations to these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed that students can experience a substantial amount of stress, which in turn can lead to negative academic outcomes or health problems. Sources of stress (stressors) include academic-related issues (such as examinations or the clinical environment), personal factors (such as relationships), and their economic situation (such as debt and student loans) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. While there has been work conducted in this area involving medical students [ 8 , 9 , 10 , 11 , 12 , 13 ], dental students [ 14 , 15 , 16 , 17 ], and nursing students [ 6 , 7 ], it has not been researched to the same extent with pharmacy students.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 10676 college/university students were included in this study and the prevalence of mental disorder was 21.4%. Although this result was lower than the nding (28.0%) from a survey conducted in Finnish university students [20], it was a little higher than results of a cross-national mental health survey (20.3%) [21] and another one (19.0%) from Hungary [22], all above studies were conducted among college students using the GHQ-12. These differences might be attributed to racial, cultural diversities, and socioeconomic disparities [23,24].…”
Section: Discussionmentioning
confidence: 72%